BNT162b2 immunization-related myocarditis in adolescents and consequent hospitalization: Report from a medical center - Chen-Wei Yen; Jung Lee; Ya-Ting Chang; En-Pei Lee; Chang-Teng Wu; Yi-Jung Chang (Pediatrics and Neonatology)
Background: To investigate Pfizer-BioNTech 162b2 mRNA COVID-19 vaccine (BNT162b2) immunization-related myocarditis and describe the risk factors for consequent hospitalization in the pediatric intensive care unit (PICU) in children between 12 and 18 years. Methods: Children and adolescents 12 years of age and older who presented with discomfort after BNT162b2 immunization (BNTI) and visited pediatric emergency room (PER) at Chang Gung Memorial Hospital from September 22, 2021 to March 21, 2022, were included for analysis. Results: 681 children presented with discomfort after BNTI and visited our PER. The mean age was 15.1 ± 1.7 years. Three hundred and ninety-four (57.9%) and 287 (42.1%) events were after 1st and 2nd dose, respectively. 58.4% (n = 398) were male. The most common complaints were chest pain (46.7%) and chest tightness (27.0%). The median (interquartile range [IQR]) interval of discomfort after BNTI was 3.0 (1.0−12.0) days. BNTI-related pericarditis, myocarditis and myopericarditis were diagnosed in 15 (2.2%), 12 (1.8%) and 2 (0.3%) patients, respectively. Eleven (1.6%) needed hospitalization in PICU. The median (IQR) hospital stay was 4.0 (3.0−6.0) days. There was no mortality. More patients were diagnosed myocarditis (p = 0.004) after 2nd dose BNTI. PICU admission occurred more commonly after 2nd dose BNTI (p = 0.007). Risk factors associated with hospitalization in PICU were abnormal EKG findings (p = 0.047) and abnormal serum troponin levels (p = 0.003) at PER. Conclusion: Myocarditis in children aged 12−18 years occurred more commonly following 2nd dose BNTI. Most cases were of mild or intermediate severity without death. Factors predicting BNTI-related myocarditis and consequent hospitalization in PICU were abnormal EKG findings and abnormal serum troponin levels at PER in this study.